2024
DOI: 10.1038/s41467-024-47686-7
|View full text |Cite
|
Sign up to set email alerts
|

Illuminating the complete ß-cell mass of the human pancreas- signifying a new view on the islets of Langerhans

Joakim Lehrstrand,
Wayne I. L. Davies,
Max Hahn
et al.

Abstract: Pancreatic islets of Langerhans play a pivotal role in regulating blood glucose homeostasis, but critical information regarding their mass, distribution and composition is lacking within a whole organ context. Here, we apply a 3D imaging pipeline to generate a complete account of the insulin-producing islets throughout the human pancreas at a microscopic resolution and within a maintained spatial 3D context. These data show that human islets are far more heterogenous than previously accounted for with regards … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Neglecting cells from the most abundant class (i.e. β cells) could lead to a biased model due to the high biological heterogeneity of Langerhans islets (Table S2 ) 24 , considering that several algorithms are built on the hypothesis of balanced classes as inputs). To address this, we employed the Synthetic Minority Oversampling Technique (SMOTE) 25 .…”
Section: Resultsmentioning
confidence: 99%
“…Neglecting cells from the most abundant class (i.e. β cells) could lead to a biased model due to the high biological heterogeneity of Langerhans islets (Table S2 ) 24 , considering that several algorithms are built on the hypothesis of balanced classes as inputs). To address this, we employed the Synthetic Minority Oversampling Technique (SMOTE) 25 .…”
Section: Resultsmentioning
confidence: 99%
“…A recent 3D whole-pancreas imaging study reported uniform distribution of insulin volumes across pancreas regions. 38 Nevertheless, such studies are scarce, highlighting the need to improve our understanding of whole-pancreas islet distribution in 2D versus 3D.…”
Section: Discussionmentioning
confidence: 99%